PROBLEM-BASED WORKSHOPS FOR THE CARE OF INSULIN DEPENDENT DIABETICS IN BASIC HEALTH CARE - Moutinho, Daniela Goncalves Godoy; Frutuoso, Maria Fernanda Petroli (Journal of Health Care, 2017)
Introduction: Primary health care is the locus of strategy for the care of insulin-dependent diabetics, including health education groups, aiming to strengthen self-care. Objectives: To describe and to analyze problem-based workshops conducted with insulin-dependent diabetics from a primary health care unit, located in a vulnerable neighborhood. Materials and methods: An intervention-research was conducted with 14 diabetics, with average age of 62.5 years. Four meetings were organized in the form of workshops, which unfolded from the generative themes listed in the first meeting, about the difficulties of self-care. All the meetings transcriptions were analyzed according to the content analysis technique. Results: According to the participants, the main difficulties of care were: restrictive diet, relationship with health care professionals, insulin therapy, and socioeconomic matters. The strategies used were round-table conversation and food tasting. The workshops provided an opportunity for experimentation of flavors, such as sweeteners, and for various types of knowledge, so that forms of management for the difficulties have arisen from the participants' repertoire, popular knowledge and sharing of care strategies related to the territory. Conclusions: The use of workshops for the care of diabetic individuals may make the educational process more horizontal, starting from the exchange of knowledge and care management from the contexts of the group and from the problems faced in the daily life of individuals, family, community and territory. It is believed that the intervention which uses knowledge sharing becomes a potentiator of self-care.
Keywords: Health education; diabetes mellitus; primary health care; self-care; feeding